Can a Click be a Word?: Infants' Learning of Non‐Native Words. (10th March 2014) - May, Lillian; Werker, Janet F.
<x xml:space="preserve">Abstract</x> Forms that are nonlinguistic markers in one language (i.e., "tsk‐tsk" in English) may be part of the phoneme inventory—and hence part of words—in another language. In the current paper, we demonstrate that infants' ability to learn words containing unfamiliar language sounds is influenced by the age and vocabulary size of the infant learner, as well as by cues to the speaker's referential intent. When referential cues were available, infants at 14 months learned words with non‐native speech sounds, but at 20 months only those infants with smaller vocabularies succeeded. When no referential cues were present, infants at both 14 and 20 months failed to learn the same words. The implications of the relation between linguistic sophistication and non‐native word learning are discussed.